A Comprehensive Study on Field Management of Phytophthora Leaf Blight Disease of Cocoyam Taro (Colocasia esculenta L.) with Spray Regimes of Selected Fungicides in Nsukka, Southeastern Nigeria - Omeje, T. E.; Ugwuoke, K. I.; Eze, S. C.; Ezema, R. A. (Cutting-edge Research in Agricultural Sciences Vol. 3, 2020)
The resent study aims to determine the efficacy of fungicides and the spray regimes on the management of taro leaf blight of cocoyam in Nsukka, Southeastern Nigeria. Cocoyam taro (Colocasia esculenta L) is an important edible aroid tuber crop, but cocoyam leaf blight caused by Phytophthora colocasiae has been the greatest constraints to cocoyam production in Nigeria since 2009. Field trials were conducted to determine the effect of fungicides and the spray regimes on leaf growth, disease incidence; disease severity and tuber yields of cocoyam. The trials were carried out at the Department of Crop Science Research Farm, University of Nigeria, Nsukka for two planting seasons. Treatments with two fungicides (Ridomil Gold Plus, Ridomil+Champ Dp50%: 50% mixture and control) and five spray regimes (No spray, weekly spray, 2nd weekly spray, 3rd weekly spray and 4th weekly spray regimes) were laid out in a 3 x 5 factorial in randomized complete block design (RCBD) with three replications. Results showed that fungicide treatments had significant (P < 0.05) variation on number of leaves/stand, disease incidence, disease severity and tuber yields/hectare in both cropping seasons. Thus, there was no significant (P < 0.05) differences between Ridomil and Ridomil+Champ (50%:50%) mixture) on all measured parameters in both cropping seasons. ANOVA of disease incidence revealed significant (P < 0.05) variation among the fungicides at all trial periods in early season planting at 90 DAP, Ridomil treated plots had the highest disease incidence compared to other fungicides options, while the least disease incidence was scored by the control treated plots. The fungicides and the spray regimes significantly reduced taro leaf blight, improved growth and yields. Ridomil treated cocoyam plots at weekly spray regimes performed best compared to other fungicides and the spray regime treatment options. In addition to adoption of high yielding resistant cultivar(s), weekly foliar spraying of Ridomil or Ridomil+Champ should be incorporated into taro leaf blight control through integrated disease management (IDM) in Nsukka, Southeastern Nigeria.